Efficient Long-PCR Site-Specific Mutagenesis of a High GC Template - Vladimir Chouljenko; Sukhanya Jayachandra; Galina Rybachuk; Konstantin G. Kousoulas (BioTechniques)
A long PCR method was developed for the efficient site-specific mutagenesis of herpes simplex virus (HSV-1) DNA fragments with high GC content. In this protocol, a PCR product was partially extended first using a cloned DNA fragment. The final mutagenized fragment was produced after a second extension using another PCR product and final amplification using external primers. The sequential use of two extension reactions increased the predicted frequency of the engineered mutation in the final product to 100%. This method was used to generate a mutated glycoprotein K (gK) gene specified by HSV-1. A recombinant virus that carried the mutated gK gene caused extensive cell fusion of infected cells.